2018
DOI: 10.1210/js.2018-00079
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia in Diabetes Mellitus: Implications for Pediatric Care

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM). It is estimated that the risk of CVD in diabetes mellitus (DM) is 2 to 10 times higher than in the general population. Much of this increased risk is thought to be related to the development of an atherogenic lipid profile, in which hypertriglyceridemia is an essential component. Recent studies suggest that dyslipidemia may be present in children and adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 115 publications
0
14
0
1
Order By: Relevance
“…Hypertriglyceridemia is often associated with T1DM and T2DM [134][135][136]. Cholesterol ester transfer protein (CETP) exchanges cholesterol and triglycerides between very low-density lipoprotein and HDL [137].…”
Section: Changes In Lipid Metabolism At the Origin Of Atherosclerosismentioning
confidence: 99%
“…Hypertriglyceridemia is often associated with T1DM and T2DM [134][135][136]. Cholesterol ester transfer protein (CETP) exchanges cholesterol and triglycerides between very low-density lipoprotein and HDL [137].…”
Section: Changes In Lipid Metabolism At the Origin Of Atherosclerosismentioning
confidence: 99%
“…Recent research has shown that cardiovascular diseases are the leading reasons for morbidity and mortality in diabetes [ 11 , 12 ]. The hyperglycemia intensifies and promotes the glycation of proteins, which is a nonenzymatic attachment of sugars to the free amino groups of proteins that can accelerate the occurrence of serious cardiovascular problems.…”
Section: Introductionmentioning
confidence: 99%
“…Macrovascular angiopathies involving coronary or cerebral vasculature are the prime causes of deaths in patients with diabetes mellitus [ 1 ]. Type 2 diabetes (T2D) is associated with specific lipid abnormalities and high blood pressure which ultimately expose the diabetic patients to cardiovascular complications such as angina, coronary vasculopathies, and cerebral infarcts [ 2 ]. Therefore, diabetic patients are at two to three times more at risk to develop cardiac problems than those without diabetes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%